2002
DOI: 10.1002/glia.10113
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐ribose) polymerase inhibitor increases growth inhibition and reduces G2/M cell accumulation induced by temozolomide in malignant glioma cells

Abstract: Temozolomide (TZM) is a novel methylating agent currently under investigation for treatment of recurrent high-grade gliomas. Although TZM generates a wide spectrum of methyl adducts, its cytotoxicity has been attributed to mismatch repair (MR)-mediated processing of O(6)-methylguanine:T mispairs. N3-methyladenine and N7-methylguanine adducts are promptly repaired by the base excision repair system, unless a poly(ADP-ribose) polymerase (PARP) inhibitor is combined to TZM. In this case, the repair process of N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 38 publications
3
24
0
2
Order By: Relevance
“…1A). Potentiation of TMZ-induced cytotoxicity by PARP inhibitors has been reported previously (32,33). For each of these agents, exposure to 4-AN resulted in a larger potentiation of cytotoxicity in ␤-pol null compared with wild-type cells (Figs.…”
Section: Effect Of Parp Inhibition On Sensitivity To Dna-damagingsupporting
confidence: 68%
See 1 more Smart Citation
“…1A). Potentiation of TMZ-induced cytotoxicity by PARP inhibitors has been reported previously (32,33). For each of these agents, exposure to 4-AN resulted in a larger potentiation of cytotoxicity in ␤-pol null compared with wild-type cells (Figs.…”
Section: Effect Of Parp Inhibition On Sensitivity To Dna-damagingsupporting
confidence: 68%
“…4B). Clearly, in our cell lines as well as in others (32,33,36), the repair of N-methyl DNA adducts by BER is an important determinant of TMZ-mediated cytotoxicity.…”
Section: Effect Of Parp Inhibition On Sensitivity To Dna-damagingsupporting
confidence: 53%
“…Using chemotherapy-resistant cell lines, the present study expanded on previous observations that PARP-1 inhibition results in the accumulation of tumor cells with DNA damage at the G 2 -M boundary of the cell cycle (7,27). PARP-1 inhibition with CEP-8983 in combination with SN38 or temozolomide resulted in a shift in the onset and magnitude of tumor cell accumulation at the G 2 -M boundary compared with SN38 or temozolomide treatment alone using HT29 and RH18 cells, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…There is considerable interest in developing more potent nontoxic PARP inhibitors with the possibility for use in a clinical setting. As described above, PARP inhibition results in cellular sensitization to the chemotherapeutic methylating agent TMZ, particularly in MMR-deficient cells, just as it does to the model methylating agents MMS and MNU [66,90,[93][94][95][96]. Further, preclinical studies have demonstrated that novel PARP inhibitors can enhance the antitumor activity of TMZ against mouse tumors and human colon and glioma xenograft models [72,[97][98][99].…”
Section: Potential Role Of Ber Modulators In Chemotherapymentioning
confidence: 99%